Penerapan Metode Copras dalam Pemilihan Kepala Pengendalian Mutu (Head Of Quality Control) - Joko Sunadi; Asriwan Guci; Abrar Tanjung (UIN Imam Bonjol Padang, 2023)
In the selection of the current Head of Quality Control is appointed manually based solely on the information provided in the application and the decisions that have been raised are inaccurate and cause delays causing the assessment not to be completed. In addition, when recruiting the Head of Quality Control manually, there are several things that can cause problems, such as hiring a Head of Quality Control who does not meet the criteria set by the company, carrying out a slow selection process, and others. The methodology used is the Complex Proportional Assessment (COPRAS) method, which is an approach used to collect data and develop systems and applications to assist companies in making decisions based on common problems. The calculation results with COPRAS were obtained from 10 selected employees, the highest UI score of 100 and the lowest of 52.18. Companies can find qualified managers who meet organizational standards by implementing a decision support system based on this COPRAS methodology.